FORTIFICATION EFFECT OF MIXED Chlorella sp. FLOUR AND SNAKEHEAD FISH (Channa striata) PROTEIN CONCENTRATE TOWARD QUALITY OF COOKIES - Lisa Mayanti Simanjuntak; Syahrul '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was aimed to determine the effect of cookies quality which fortified Chlorella sp. flour and snakehead fish (Channa striata) protein concentrate. The methode used in this research was experimental methode with treatment C0K0 (Control), C0K2 (0% Chlorella sp. and 10% snakehead fish protein concenterate, C2K0 (2% Chlorella sp. and 0% snakehead fish protein concenterate), and C2K2 (2% Chlorella sp. and 10% snakehead fish protein concenterate). Parameters tested were organoleptic and chemical analysis. The results showed that cookies with addition 2% of Chlorella sp. flour and 10 % of snakehead fish protein concentrate (C2K2) was the best treatment with criteria: attractive colors 8.12%, distinctive aroma of Chlorella sp. and fish protein concentrate 7.88%, the texture was slightly crunchy 7,24% and good taste 6,18%; protein content 15.57%, moisture content 1.89% and ash content 0,24%.Keywords : Cookies, Chlorella sp., Channa striata, Fish Protein Concentrate